Adaptive Forgetting: Why Predator Recognition Training Might Not Enhance Poststocking Survival. Issue 1 (22nd January 2013) - Brown, Grant E.; Ferrari, Maud C. O.; Chivers, Douglas P.
Abstract: The success of current fish restocking efforts is often hampered by poor poststocking survival of hatchery‐reared juveniles. As a result of hatchery selection, combined with a lack of ecologically relevant experience, hatchery‐reared fishes often fail to recognize and respond to potential predators following stocking into natural waterways. One commonly proposed method to enhance potential poststocking survival is to condition hatchery‐reared fishes to recognize predators prior to stocking. However, despite a wealth of laboratory and field studies demonstrating predator recognition learning in fishes, only a handful of studies have attempted to assess potential poststocking benefits, and these suggest mixed results. Our goal is to highlight possible causes of this apparent contradiction. A survey of the behavioral ecology literature highlights the exceptional degree of sophistication of predator recognition learning among prey fishes. Moreover, an emerging body of literature suggests that how long prey retain learned predator recognition is as important as what prey learn. This highly plastic retention (memory window) may confer adaptive benefits under variable conditions. Hatchery selection may result in phenotypes leading to reduced learning and/or retention of learned information. We conclude by proposing several avenues of investigation aimed at improving the success of prestocking conditioning paradigms.